STUDI PARAMETER FISIK KIMIAWI UNTUK KELIMA JENIS AIR DENGAN PERLAKUAN YANG BERBEDA - Bening Sari Gunawan; Azizah Muthmainah, Inas Nur Halimah, Evi Liviawaty, Nursahbani Komarudin, Kenny Pramudya Hermanto (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Water covers about 70 percent of the earth's surface volume. The properties of water bodies are characterized by 3 (three) main components, namely physics, chemistry and biology. Water quality is one of the most important parameters in fish farming. Water quality can be read using chemical and physical parameters. The aim of the research was to test water quality with 5 sample water treatments, consisting of P1 water only, P2 water with aeration, P3 water with aeration and zooplankton, P4 water with aeration and fish, P5 water with aeration, zooplankton and fish. Includes physical quality (temperature) and chemical quality (pH, DO, ammonia, phosphate, nitrite, nitrate, free CO2, and alkalinity). The method used is observational research through laboratory testing in the SDP FPIK lab at Padjadjaran University. From observational research on these 5 water treatments, differences in levels of pH, DO, temperature, ammonia, phosphate, nitrite, nitrate, free CO2 and alkalinity were found in each treatment.